Factors Influencing Tourist Services At Lok Baintan Floating Market In Banjarmasin City - Rahmah, Natasya Aprilia Nuzula; Kadir, Abdul; Jayen, Fredy; Amrulloh, Rifqi (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Cirebon, 2024)
The decline in the number of visitors to the Lok Baintan Floating Market from 2022 to 2023, complaints from tourists regarding seller ethics and communication, and the importance of improving service quality to maintain tourism sustainability at the Lok Baintan Floating Market are key issues. This study aims to analyze the influence of seller ethics and communication on tourist services at the Lok Baintan Floating Market, Banjarmasin City. This research uses a quantitative method with an explanatory research design, which aims to explain the relationship between variables through hypothesis testing. The research population consists of tourists visiting the Lok Baintan Floating Market, with a sample taken using purposive sampling technique. The results show that seller ethics and communication simultaneously have a significant impact on tourist services. Partially, seller ethics also significantly affect service quality, where sellers who exhibit good ethics in business and adhere to prevailing regulations tend to provide better service to tourists. Similarly, effective communication between sellers and tourists significantly contributes to improving service quality. This study concludes that enhancing seller ethics and communication skills can increase tourist satisfaction at the Lok Baintan Floating Market. The study suggests the need for training and development for sellers related to business ethics and effective communication to improve service quality and tourist experience.